Learners’ Perceptions Towards the Effectiveness of MOOC in Learning Mandarin: 从学习者视角探视MOOC在汉语学习中的应用效果 - Ling, TING Hie; Jun, Ye (Published by Confucius Institute UNS, 2000)
The Massive Online Open Course or MOOC was officially launched in Malaysia in 2012. Universiti Teknologi MARA (UiTM), as one of Malaysia's higher education institutions, also involved actively in the promotion of MOOC. Therefore, MOOC UiTM were officially established in 2019. MOOC on Foundation Mandarin (Level II) or MOOC TMC151 is one of the MOOC courses which could be found on the MOOC UiTM. MOOC TMC151 has become as the primary platform neither for the implementation of Online Distance Learning (ODL), nor blended learning during the pandemic. Hence, it is important to explore the effect of the application of MOOC TMC151 in Mandarin learning. To that reason, this study included 36 students who enrolled